2008
DOI: 10.1099/vir.0.83578-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraventricular infusion of anti-prion protein monoclonal antibodies on disease progression in prion-infected mice

Abstract: It is well known that anti-prion protein (PrP) monoclonal antibodies (mAbs) inhibit abnormal isoform PrP (PrPSc) formation in cell culture. Additionally, passive immunization of anti-PrP mAbs protects the animals from prion infection via peripheral challenge when mAbs are administered simultaneously or soon after prion inoculation. Thus, anti-PrP mAbs are candidates for the treatment of prion diseases. However, the effects of mAbs on disease progression in the middle and late stages of the disease remain uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…2). These factors were chosen with reference to cell surface expression of those receptors on MSCs in previous studies (50) and to the pathway and networks of receptors and their ligands obtained using Ingenuity Pathway Analysis 5.0 (Ingenuity System, Inc., Redwood City, CA). The migration of hMSCs to the brain extracts of prion-infected mice was significantly decreased when hMSCs were pretreated with antibodies against CCR3, CCR4, CCR5, CXCR3, and CXCR4 compared to the migration of untreated hMSCs (P Ͻ 0.05, Dunnett's test) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). These factors were chosen with reference to cell surface expression of those receptors on MSCs in previous studies (50) and to the pathway and networks of receptors and their ligands obtained using Ingenuity Pathway Analysis 5.0 (Ingenuity System, Inc., Redwood City, CA). The migration of hMSCs to the brain extracts of prion-infected mice was significantly decreased when hMSCs were pretreated with antibodies against CCR3, CCR4, CCR5, CXCR3, and CXCR4 compared to the migration of untreated hMSCs (P Ͻ 0.05, Dunnett's test) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, only a few of these inhibitors, such as amphotericin B and its derivative (13), pentosan polysulfate (14), porphyrin derivatives (27), certain amyloidophilic compounds (25), and FK506 (37) have been reported to prolong the survival of prion-infected mice even when administered in the middle-late stage of infection but still before clinical onset. We recently reported that intraventricular infusion of anti-PrP antibodies (50) slowed down the progression of the disease even when initiated just after clinical onset. However, in addition to inhibition of PrP Sc formation, the protection of neurons or restoration of degenerated neurons is thought to be important for functional recovery.…”
mentioning
confidence: 99%
“…Recently, passive immunization has been extensively investigated ( Figure 1). 63,68,96,[108][109][110][111][112][113] Transgenic expression of the µ heavy chain of anti-PrP antibody 6H4 in PRNP -/-mice was found to completely prevent prion infection after intraperitoneal PrP Sc administration. 68 The most common way of administering anti-prion antibodies to prion-infected mice is peripherally.…”
Section: Passive Immunizationmentioning
confidence: 99%
“…Treatment initiated at 60 days was found to elongate the lifespan of the mice. 109 However, another group has reported that the administration of anti-PrP antibodies into the CNS has strong adverse effects. 93 In their study, three different purified, endotoxin-free, PrP C -specific monoclonal antibodies were stereotaxically injected into the right hippocampus of C57BL/10 mice.…”
Section: Passive Immunizationmentioning
confidence: 99%
“…In clinical trials, pentosan polysulfate seems to extend the survival of several patients beyond the mean but appears unable to arrest the progression of the disease (4,45). Recently, we demonstrated that intraventricular infusion of an anti-PrP monoclonal antibody (MAb) could antagonize disease progression even when initiated after clinical onset, although the distribution of the MAb was largely restricted to the hippocampus and thalamus (53). Thus, improved delivery of the MAb may enhance its beneficial effects.…”
mentioning
confidence: 99%